Product rating statistics as consumer search aids - Guan, Chong (2020)
Online product review forums commonly provide consumers with averages of product ratings given by reviewers. Some also provide frequency distribution of ratings in the form of a histogram. The authors argue that consumers use these statistics as search aids when reading reviews. Provision of the average rating statistic affects consumers' reading of reviews through confirmation or disconfirmation of their expectancies about the product in question. However, provision of the distribution statistics attenuates this effect because it alerts consumers to divergent opinions. An eye-tracking experiment that simulated a forum visit demonstrates these effects. The experiment also shows that as a result of these effects, average rating provision causes consumer attitude toward the product to be more extreme, whereas rating distribution provision reduces this polarization. Further, supporting the expectancy confirmation account, results show that consumers with a high need for cognition exhibit a greater response to average rating provision than those with a low need. The findings suggest the benefits to marketers of tracking the number of negative reviews read by consumers and displaying positive reviews and negative reviews separately. The findings also identify circumstances that call for greater effort by marketers when responding to reviews.